A review of the literature on the causal relationships between occlusal factors (OF) and temporomandibular disorders (TMD) II: analytical epidemiological studies of observation - Rodolfo Acosta-O; Blanca P. Rojas-S (Universidad de Antioquia, 2006)
This is the second in a series of articles that have as purpose to present a literature review about the causal relationship between occlusal factors (OF) and temporomandibular disorders (TMD). In this article, Analytic epidemiologic studies are presented and analyzed. Such analytic studies have a higher degree of confidence in the scientific evidence pyramid, and may offer more concrete conclusions about possible relationships between FO and TMD. The analysis of the studies reported in this article did not find any causal relationship between OF and the development of TMD. Although there was an association of some of the OF and TMD, many of them could be better seen as the consequence and not the cause of a TMD. Additionally, even though in the longitudinal studies certain OF were correlated to signs or symptoms of TMD, none of the OF could be associated to the development of a TMD or to any of the diagnostic categories of TMD.